Optimasi K Nearest Neighbour dengan Algoritma Genetika - Lesmono, Ibnu Dwi; Dwi Praba, Ardian (Jurnal Teknik Informatika, 2017)
AbstractÃ¢â‚¬â€ Data mining is a field that are merged from several fields which brings together techniques from machine learning, pattern recognition, statistical databases, and visualization for information retrieval problem recognition and large databases. Classification is the process of the invention of the model which describe and distinguish classes or the concept that aims to be used to predict the class of the object label kelasya is not yet known. Many algorithms that can be used in solving the problem of classification in data mining one is K Nearest neighbour or K-NN. K-NN is the algorithm that aims to find new patterns in the data with the use of existing data patterns with the new data. The k-NN algorithm is one of the most widely used in the classification of learning based on terawasi, but the K-NN has problems on the determination of the optimal K parameter resulting in lower accuracy. In this paper will be discussed how the influence of K-NN algorithm if combined with genetic algorithm for parameter optimization of K.IntisariÃ¢â‚¬â€ Data mining adalah bidang yang digabung dari beberapa bidang keilmuan yang menyatukan teknik dari pembelajaran mesin pengenalan pola, statistik database, dan visualisasi untuk pengenalan permasalahan pengambilan informasi dan database yang besar. Klasifikasi adalah proses penemuan model yang menggambarkan dan membedakan kelas atau konsep yang bertujuan agar bisa digunakan untuk memprediksi kelas dari object yang label kelasya belum diketahui. Banyak algoritma yang bisa digunakan dalam menyelesaikan masalah klasifikasi dalam data mining salah satunya adalah K Nearest neighbour atau K-NN. K-NN adalah algoritma yang bertujuan untuk menemukan pola baru dalam data dengan menggunakan pola data yang sudah ada dengan data yang baru. K-NN adalah salah satu algoritma yang paling banyak digunakan dalam klasifikasi berdasarkan pembelajaran terawasi, namun K-NN memiliki masalah pada penentuan parameter K yang optimal sehingga menghasilkan akurasi yang rendah. Dalam makalah ini akan dibahas bagaimana pengaruh algoritma K-NN jika digabung dengan algoritma genetika untuk optimasi parameter K.Ã‚Â Kata Kunci: Klasifikasi, Optimasi, K Nearest Neighbour, Algoritma Genetika.